The Property Characterization of α-Sialon/Ni Composites Synthesized by Spark Plasma Sintering - Adeniyi, Adedayo Sherif; Amir Azam, Khan; Bilal, Anjum Ahmed; Abbas, Saeed Hakeem; Faheemuddin, Patel; Akolad, Idris Bakare; Anwar, Ul-Hamid; Muhammad Ali, Ehsan; Tahir, Irfan Khan (MDPI AG, 2019)
This study investigates the effect of micron-sized nickel particle additions on the microstructural, thermal, and mechanical property changes of α-sialon ceramic composites. The α-sialon/Ni composites were synthesized with an increasing amount of Ni (10–40 wt.%) using the spark plasma sintering technique and nanosized alpha precursors at a relatively low synthesis temperature of 1500 ◦C with a holding time of 30 min in each case. The density of the samples increased with the increase in Ni content of up to 15 wt.% and, with the further increase in Ni content, it became almost constant with a slight decrease. Furthermore, thermal conductivity and thermal expansion properties of Ni-sialon composites improved slightly with the inclusion of 10 wt.% Ni. The addition of Ni to α-sialon matrix resulted in a decrease in the hardness of the composites from HV10 21.6 to HV10 16.3, however the presence of Ni as a softer interfacial phase resulted in a substantial increase in the fracture toughness of these composites. Fracture toughness was found to increase by approximately 91% at 40 wt.% Ni addition.